Implementasi Mutu Pelayanan Farmasi Klinik di Puskesmas Kabupaten Lombok Tengah - Almahera, Almahera (FORIKES, 2024)
Pharmaceutical service standards are guidelines and indicators for pharmaceutical personnel in providing pharmaceutical services. This research aimed to determine the quality of clinical pharmacy services. This research applied a descriptive study. Data was collected through direct observation of research subjects using clinical pharmacy indicators, document review, and interviews. Next, data analysis was carried out using descriptive methods. The results of the study showed that for clinical pharmacy services, the prescription review stage was not appropriate, labeling was not appropriate, drug delivery and information were not appropriate, service time was appropriate, polypharmacy was not appropriate, documentation of drug information services was not appropriate, the number of counseling patients was not appropriate, visite documentation was not appropriate. appropriate, documentation of monitoring of drug side effects is inappropriate, documentation of monitoring of drug therapy is inappropriate. Cost per prescription visit = 77.38%, drug items per prescription = 77.78%, drug delivery with information = 68%, non-concocted prescription service time = 4.45%, polypharmacy compounded prescription service time = 0.35%, drug costs per prescription visit = 4,089 rupiah, drug items per prescription = 2.80 items, generic preparations = 100%, antibiotics for non-specific diarrhea = 19.29%, administration of ORS for diarrhea = 41.89%, administration of zinc for diarrhea = 53.23%, antibiotics in non-pneumonia = 18.77%, use of injections = 7.01%. It was concluded that the clinical pharmacy service indicators at the Central Lombok District Health Center did not meet standards and service quality needed to be improved.Keywords: health center; clinical pharmacy services; indicator ABSTRAK Standar pelayanan kefarmasian merupakan pedoman dan indikator bagi tenaga kefarmasian dalam menyelenggarakan pelayanan kefarmasian. Penelitian ini bertujuan untuk mengetahui mutu pelayanan farmasi klinik. Penelitian ini menerapkan studi deskriptif. Data dikumpulkan melalui observasi langsung kepada subjek penelitian dengan menggunakan indikator farmasi klinik, telaah dokumen, dan wawancara. Selanjutnya dilakukan analisis data dengan metode deskriptif. Hasil penelitian menunjukkan bahwa untuk pelayanan farmasi klinik, tahap pengkajian resep tidak sesuai, pelabelan tidak sesuai, penyerahan obat dan informasi tidak sesuai, waktu pelayanan sesuai, polifarmasi tidak sesuai, dokumentasi pelayanan informasi obat tidak sesuai, jumlah pasien konseling tidak sesuai, dokumentasi visite tidak sesuai, dokumentasi monitoring efek samping obat tidak sesuai, dokumentasi pemantauan terapi obat tidak sesuai. Biaya per kunjungan resep = 77,38%, item obat per resep = 77,78%, penyerahan obat disertai informasi = 68%, waktu pelayanan resep non racikan = 4,45%, waktu pelayanan resep racikan polifarmasi = 0,35%, biaya obat per kunjungan resep = 4,089 rupiah, item obat per resep = 2,80 item, sediaan generik = 100%, antibiotik pada diare non spesifik = 19,29%, pemberian oralit untuk diare = 41,89%, pemberian zink untuk diare = 53,23%, antibiotik pada non-pneumonia = 18,77%, penggunaan injeksi = 7,01%. Disimpulkan bahwa indikator pelayanan farmasi klinik di Puskesmas Kabupaten Lombok Tengah belum memenuhi standar dan perlu dilakukan perbaikan kualitas pelayanan.Kata kunci: puskesmas; pelayanan kefarmasian klinik; indikator